Single-Cell Genomic Sequencing of Three Peritrichs (Protista, Ciliophora) Reveals Less Biased Stop Codon Usage and More Prevalent Programmed Ribosomal Frameshifting Than in Other Ciliates - Chen, Xiao; Wang, Chundi; Pan, Bo; Lu, Borong; Li, Chao; Shen, Zhuo; Warren, Alan; Li, Lifang (Frontiers in Marine Science, 2020)
Peritrichs are one of the largest groups of ciliates with over 1,000 species described so far. However, their genomic features are largely unknown. By single-cell genomic sequencing, we acquired the genomic data of three sessilid peritrichs (Cothurnia ceramicola, Vaginicola sp. and Zoothamnium sp.2). Using genomic data from another 53 ciliates including 14 peritrichs, we reconstructed their evolutionary relationships and confirmed genome skimming as an efficient approach for expanding sampling. In addition, we profiled the stop codon usage and programmed ribosomal frameshifting (PRF) events in peritrichs for the first time. Our analysis reveals no evidence of stop codon reassignment for peritrichs, but they have prevalent +1 or -1 PRF events. These genomic features are distinguishable from other ciliates and our observations suggest a unique evolutionary strategy for peritrichs.